Quality monitoring of intellectual and developmental disabilities systems in the US: Assessing the utility and applicability of selected National Core Indicators to national and state priorities - Bradley, Valerie; Hiersteiner, Dorothy (Frontiers in Rehabilitation Sciences, 2022)
This article provides historical context on the evolution of performance measures for system improvement, examines the perspectives and insights of state public managers on the use and utility of NQF-endorsed outcome measures from the NCI®-IDD In-Person Survey (IPS) for quality improvement, and discusses the necessity of ensuring that outcome measures align with public policy goals.